Reproducibility of thoracic and abdominal aortic wall measurements with three‐dimensional, variable flip angle (SPACE) MRI. Issue 1 (31st December 2013) - Mihai, Georgeta; Varghese, Juliet; Lu, Bo; Zhu, Hong; Simonetti, Orlando P.; Rajagopalan, Sanjay
<x xml:space="preserve">Abstract</x> Purpose To evaluate the reproducibility and repeatability of high‐resolution, isotropic thoracic and abdominal aortic wall measurements, and determine the implications they have on the number of subjects necessary for future clinical trials. Materials and Methods Using a T1‐weighted three‐dimensional MRI SPACE sequence, we evaluated the interobserver, intraobserver, and scan–rescan variability of isotropic thoracic and abdominal aortic wall measurements in 15 cardiovascular diseased patients and 6 normal volunteers. Main outcome analyses were intracorrelation coefficient (ICC), mean relative error (mRE), and sample size calculation at 80% power to be used to compare placebo group and treatment group means in future two‐arm randomized clinical trials. Results Excellent reliability, ICC > 0.8 (P < 0.001) and small mRE < 10% were demonstrated for the interobserver, intraobserver, and scan–rescan variability for all investigated measures: lumen area (LA), outer wall area (OWA), wall area (VWA), total wall volume (TWV), and percentage wall volume (%WV). Sample size calculation revealed slightly different sample size per treatment arm for thoracic and abdominal aorta segments (maximum number of subjects: 352 subjects for thoracic segment versus 421 subjects for abdominal segment for LA at 5% difference, and minimum of 3 thoracic versus 4 abdominal subjects needed for %WV evaluation at 25% difference). Conclusion Our study demonstrates the reproducibility and repeatability of SPACE aortic plaque measurements, and gives insight into the number of subjects needed for the design of therapeutic studies in aortic atherosclerosis. J. Magn. Reson. Imaging 2015;41:202–212. © 2013 Wiley Periodicals, Inc.